ICHTHYOFAUNAL DIVERSITY AND AQUACULTURE POTENTIAL OF SOME FLOODPLAIN WETLANDS IN THE DISTRICT OF NORTH 24 PARGANAS, WEST BENGAL - Mondal, Debjit Kumar; Das, Bipul Kumar; Kaviraj, Anilava (Journal of the Inland Fisheries Society of India, 2016)
Five floodplain wetlands, locally called â€˜baorâ€™, located in West Bengal were studied in the year 2003. Sixty speciesÂ (including five exotic species) belonging to twenty-four families were recorded in the baors. Stocking and harvestingÂ of carps is practiced in the baors on annual basis. Maximum yield (901.9 kg/ha) of carps was recorded from GopalnagarÂ baor during 2000-2001. The major carps are harvested during a specified season while the small fish are harvestedÂ throughout the year without any regulation. Gudusia chapra, Amblypharyngodon mola, Mystus sp. and Puntius sp.Â constitute a significant percentage of the total catch. A detailed account of ichthyofaunal diversity and aquacultureÂ potential of the baors have been discusse